정부별 한국 공공분쟁의 현황과 추세 - 김강민; Gang Min Kim; 임재형; Jae Hyoung Lim; 가상준; Sangjoon Ka; 안순철 (한국행정연구, 2014)
본 연구는 정부별로 공공분쟁의 특징은 무엇이었으며, 임기별로 나타나는 일반적인 특징이 있는지 알아보는 것을 목적으로 하였다. 특히 공공분쟁이 정부별로 공통적인 특징 혹은 뚜렷한 경향을 보이며 발생하였는지 알아보는 것을 목적으로 하였다. 분석을 통해 한국 공공분쟁에 가장 높은 비율을 차지하는 분쟁은 노동분쟁이지만 지역분쟁과 계층분쟁의 발생이 최근에 들어 급격히 늘어나고 있음을 발견할 수 있었다. 한국의 공공분쟁을 정부별로 구분해 살펴보면 상대적으로 지역분쟁의 증가와 노동분쟁의 감소를 찾을 수 있다. 이에 따라 민/민 분쟁은 감소하고 관/관 분쟁이 증가하고 있는 상황이다. 종합적으로 4개 정부 20년을 돌아보면 한국의 공공분쟁에 커다란 변화가 있다고 말할 수 있다. 과거 한국의 고질적인 분쟁이었던 노동분쟁은 아직도 심각한 수준으로 남아 있지만, 이에 더하여 계층분쟁과 지역분쟁이 크게 확대되는 모습을 보이며 한국 공공분쟁의 지형을 바꾸고 있는 것이다. 이들의 증가 속도가 매우 빠르다는 점에서 조만간 계층분쟁과 지역분쟁이 노동분쟁을 뛰어넘어 한국의 공공분쟁은 계층분쟁과 지역분쟁으로 대표되는 시기를 맞이하게 될 것이다. 한편 이념분쟁의 증가세는 발견되지 않았지만 많은 공공분쟁들의 내면에는 이념적 대립이 잔존하고 있어 이념분쟁은 잠재적으로 커다란 사회 문제라고 말해도 과언이 아니다. 본 연구는 한국 공공분쟁을 정부별, 임기별로 분석함으로써 한국 공공분쟁의 추세 및 발생에 있어 중요한 특징을 찾았다는 점에서 의미를 찾을 수 있었다. The purpose of this study is to examine characteristics of public disputes of the 4 governments from the Youngsam Kim government to the Myungbak Lee government and to find whether the occurrence of particular public dispute is associated with presidential term. Analyses on Korean public disputes in 4 governments show that labor disputes have the highest percentage of the overall public disputes for 20 years; however, study discovers that the rates of regional disputes and class disputes rapidly have increased in recent. Accordingly, the rate of public disputes between governments increases while the rate of public disputes between private groups decreases. It implies that there has been a sea change in public disputes during 20 years. The study sincerely expects that regional disputes and class disputes overtake labor disputes soon. A rapid increase of regional disputes and class disputes will change characteristics and trends of Korean public disputes. However, the study can`t find the percentage of ideological disputes has increased even though the Korean society suffers from ideological polarity between conservatives and liberals. But, the fact that many public disputes internally contain ideological confrontation even though they are not originally classified as ideological disputes implies that ideological disputes will become a serious social problem in Korea. The study is of importance because it finds trends and status of Korean public disputes by analyzing characteristics of public disputes by each administration and presidential term.